Imaging characteristics of cerebral small vessel disease in high⁃altitude plateau - WANG Jun⁃shan; ZHAO Wei⁃wei; ZHUO Ma; CHEN Yu⁃xiu; ZHAO Yu⁃hua; YUAN Jing (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To analyze the distribution characteristics of imaging biomarkers in cerebral small vessel disease (CSVD) in high⁃altitude plateau, investigate interrelationships among imaging features, and identify influencing risk factors for high CSVD burden. Methods A total of 131 CSVD patients diagnosed and treated at People's Hospital of Xizang Autonomous Region between January 2021 and December 2022 were enrolled. Clinical data were collected, and brain MRI was performed to assess white matter hyperintensity (WMH), lacunar infarcts (LACI), cerebral microbleeds (CMBs), and enlarged perivascular space (EPVS), with subsequent calculation of the total CSVD burden score. The distribution patterns of CSVD imaging markers were analyzed. Spearman rank correlation analysis was used to investigate the association among imaging biomakers, including WMH, LACI, CMBs and EPVS. Univariate and multivariate Logistic regression analyses were applied to examine risk factors for high CSVD burden. Results Total 131 patients with CSVD were divided into high CSVD burden group (1-4 points, n = 85) and low CSVD burden group (0 point, n = 46) according to total CSVD burden score. Compared to the low CSVD burden group, the high CSVD burden group exhibited significantly older age (t = ⁃ 5.410, P = 0.000) and a higher prevalence of hypertension (χ2 = 14.853, P = 0.000). Among patients with CSVD in high ⁃altitude plateau, the prevalence of WMH was 95.42% (125/131); LACI accounted for 34.35% (45/131), and were commonly located in the basal ganglia region; CMBs were predominantly of the mixed type (40.54%, 15/37); the prevalence of EPVS was 54.96% (72/131). Spearman rank correlation analysis revealed that CMBs were positively correlated with WMH (rs = 0.255, P = 0.003) and LACI (rs = 0.289, P = 0.001). Logistic regression analysis revealed that older age (OR = 1.056, 95%CI: 1.026-1.088; P = 0.000) and hypertension (OR = 2.482, 95%CI: 1.071-5.753; P = 0.034) were risk factors for high CSVD burden. Conclusions Prevention and management strategies for CSVD in these populations should prioritize elderly individuals and hypertensive patients. While high⁃altitude environment may exacerbate cerebrovascular pathology, their specific mechanistic roles require further investigation.